In Search of Domains in Smart Specialisation - Case Study of Three Nordic Regions - Mäenpää, Antti; Antti Mäenpää and Jukka Teräs (Zenodo, 2018)
The European Union has promoted regional smart specialisation strategies for some years, and several studies on this topic have focused on key concepts such as the entrepreneurial discovery process and good implementation practices. However, the definition and the role of the domain in regional smart specialisation settings is largely missing, despite it being an important outcome of a successful entrepreneurial discovery process. This article aims to fill this research gap by establishing what a domain entails as a theoretical concept, its role in the entrepreneurial discovery process and how it has featured in regional smart specialisation strategies. Our study analyses and compares three smart specialisation strategies in the Nordic regions of Lapland (Finland), Värmland (Sweden) and Nordland (Norway), focusing on the understanding and adaptation of the domain concept. The results indicate that the regions have managed to establish domains, even though the concept itself has not been adopted in the regions because of insufficient clarification of the term. The paper is published by the European Journal of Spatial Development (EJSD) . The previous version of the journal was host by Nordregio . The same version of the paper can also be found in NordPub .